Differential effect of trypsin on infectivity of Chlamydia trachomatis: loss of infectivity requires cleavage of major outer membrane protein variable domains II and IV. - Su, H (1988)
The initial interaction of chlamydiae with host cells is not well understood. Chlamydial cell surface components that function in attachment are key virulence factors, and their identification is critical for understanding the pathogenic strategies of this very successful parasite. We used trypsin proteolysis of chlamydiae to define surface components that function in chlamydia-host cell interactions. We found that trypsin had a differential effect on the infectivity of Chlamydia trachomatis serovars B and L2 for HeLa 229 cells. Trypsin treatment resulted in a significant loss of attachment and infectivity of serovar B but had no effect on the infectivity of serovar L2. Fluorograms of chlamydiae metabolically labeled with 14C-amino acids and treated with trypsin showed that the major outer membrane protein (MOMP) of both serovars was cleaved. Evidence for two trypsin cleavage sites was found for the serovar B MOMP. One cleavage site was located between lysine 145 and valine 146 in variable domain (VD) II of the protein. The second site was located between lysine 309 and threonine 310 in VD IV. In contrast, the serovar L2 MOMP was cleaved only at lysine 309 in VD IV. These results suggest a functional role for MOMP in chlamydial attachment and implicate VDs II and IV of MOMP in this interaction.